Population densities and diversity of Calliphoridae (Diptera) around a nickel-copper smelter at Monchegorsk, Northwestern Russia - Kozlov, Mikhail; Whitworth, Terry (Entomologica Fennica, 2002)
In the summer of 2000, we collected blowflies (Calliphoridae) in ten sites around the Severonikel smelter on the Kola Peninsula. Meat-baited funnel traps (three per site), operated from June 10 to August 30, yielding 973 specimens of ten blowfly species; eight species are reported from the Kola Peninsula for the first time. The maximum catch (495 individuals), obtained at the site located 1 km from the smelter, was due to the synanthropic preferences of the two most common species, Protophormia terraenovae and Cynomya mortuorum. Neither total abundance nor diversity of blowflies attracted by meat baits changed along the pollution gradient.